PLGA nanoparticles and microspheres for controlled drug delivery. - Gong, Tianxing. (2009)
Drug delivery systems are attracting more and more funding in recent years among other hot research topics. Producers and consumers increasingly realize the importance of such drug delivery mechanisms and the benefits they bring to human beings. Typically, polymers are the best drug delivery carriers, as compared to metals. Their degraded products are less toxic and easy to be excreted from the body. Moreover polymers are more flexible than ceramics and provide good patient compliance. The selection of polymers is limited by biocompatibility, biodegradability and monomers’ toxicity. Few polymers are available and safe to be in drug delivery system, and the pending time in which the material suppliers are waiting for the approval of polymer safety from the national authority is decades of time. Therefore, the development of currently available biopolymers is timely and the most economic option. Poly [(lactic acid)-co-(glycolic acid)] (PLGA) is one of biopolymers being widely used for years. One advantage of PLGA is bioerosion products, oligomers or monomers, which are biocompatible with the physiological environment. Interests in developing shape of microspherical particles, as part of entire drug delivery system, are evident in our school biomaterial laboratory. Moreover, the size of those microspheres and surface conditions are of importance as well, since they affect absorption into bloodstream. In my final year project (FYP), the focus is on developing PLGA microspheres of 2μm in diameter and smooth surfaces by using the spray drying technique. PLGA has several molar compositions, and in my project, I only tried PLGA (75/25) and PLGA (53/43). The solvents used to dissolve the polymer are acetone, which is more important, and chloroform. From my research I obtained the desired results and learnt precious information from these experiments. More importantly, I managed to put together the ways to predict particle size and optimal operational parameters, which could benefit other researchers in future attempts.